2002
DOI: 10.1007/s00429-002-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

GAP-43 Immunoreactivity in the brain of the developing and adult wallaby ( Macropus eugenii )

Abstract: We have examined the distribution of immunoreactivity for GAP-43 in the developing and adult brain of a diprotodontid metatherian, the tammar wallaby ( Macropus eugenii). The distribution of GAP-43 immunoreactivity in the neonatal wallaby brain was strikingly heterogeneous, in contrast to that reported for the newborn polyprotodontid opossum. Immunoreactivity for GAP-43 in the developing wallaby brain showed a caudal-to-rostral spatiotemporal gradient, with the brainstem well in advance of the telencephalon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…The ages of pouch young wallabies were determined either directly by noting the elapsed time from the date of birth, which was designated P0, or from measurements of head length and reference to a chart of head lengths of animals of known age, which is accurate to within 8 2 days. The tissue used for the developmental series had been used for a previous study of GAP-43 development in the brain of this species [Hassiotis et al, 2002].…”
Section: Animalsmentioning
confidence: 99%
“…The ages of pouch young wallabies were determined either directly by noting the elapsed time from the date of birth, which was designated P0, or from measurements of head length and reference to a chart of head lengths of animals of known age, which is accurate to within 8 2 days. The tissue used for the developmental series had been used for a previous study of GAP-43 development in the brain of this species [Hassiotis et al, 2002].…”
Section: Animalsmentioning
confidence: 99%
“…Immunohistochemical methods to reveal GAP-43-like immunoreactivity in this material have been described previously [Hassiotis et al, 2002]. This antibody recognizes an epitope on both kinase C phosphorylated and dephosphorylated forms of GAP-43.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The manner in which the newborn tammar redirects its movements when it reaches the edge of the pouch and enters it might indicate a response to either the odor of the pouch or the texture of its moist hairless skin [Tyndale-Biscoe, 2005]. Olfactory knobs have been identified in the nasal epithelium of the newborns of several species of diprotodont and polyprotodont marsupials [Gemmell and Nelson, 1988;Gemmell and Rose, 1989;Gemmell and Selwood, 1994] and well-developed nerve fibers have been shown to connect the olfactory epithelium to the relatively large olfactory bulbs at birth in the native cat and the tammar [Hill and Hill, 1955;Hassiotis et al, 2002]. These findings stand in contrast to the delayed development of neuronal activity in the olfactory bulb of the tammar, investigated in vivo under anesthesia [Ellendorff et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…most differentiated cellular architecture at birth. Sections immunoreacted for GAP-43 showed that the vestibular area in general typically featured low immunoreactivity compared with other neural structures [Hassiotis et al, 2002], suggesting that there has been minimal development of afferents to the nuclei at birth. The LVe, however, featured more prominent immunoreactivity, perhaps indicating a greater degree of afferent development than other areas in the vestibular complex.…”
Section: Discussionmentioning
confidence: 99%
“…These sections have been used in previous studies on wallaby development, with description of control procedures [Hassiotis et al, 2002]. Deparaffinized sections were incubated in 3% H 2 O 2 in anhydrous methanol for 30 min to block endogenous peroxidase activity.…”
Section: Immunohistochemistrymentioning
confidence: 99%